PENERAPAN PEMBELAJARAN BERBASIS ALTERNATIVE SOLUTIONS WORKSHEET UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF - Usman Aripin; Ratni Purwasih (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2017)
This research is motivated by the low ability of mathematical creative thinking of high school students of class X IPA. To overcome these problems required one of the learning models are expected to develop creative thinking skills and mathematical disposition of students is based on Alternative Solutionss Worksheet. Through this learning, students are directly involved and learn to come up with ideas in solving open ended problems, so that the students interest to be active during the learning process. It is expected that through this learning, students become motivated, resilient.The output form of this research is an open ended alternative worksheet solution which can be utilized by teachers for teaching materials. The research method used is quasi experimental with design form of Nonequivalent Control Group Design, where the research subjects are not grouped randomly. The data in this study were collected through the pretest and postes of mathematical ability as well as the scale of the students' mathematical disposition. The results of this study are classes that use learning alternative solution worksheet better than conventional class.